Religious Spirituality – Cognitive Behaviour Therapy Untuk Meningkatkan Self-Confidence Dalam Social Interaction Anak Usia Dini - Dwi Bhakti Indri M (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2016)
Cognitive behavioral therapy can improve self-confident in social interaction that experienced by children. CBT of implementation can be integrated with religious, spirituality, and play therapy. Those have been studied theoretically and practically. There are various advantages in integrating religious, spirituality, and play techniques in cognitive behavioral therapy for early childhood. Thus, the intervention and development of counseli are expected to be more effective and efficient. This article try to explain about integrated religious and spirituality into cognitive behavioral therapy without releasing the element of play for the child.